Improving the availability of trade finance during financial crises - Marc Auboin; Moritz Meier-Ewert (World Trade Organization (WTO), 2003)
An analysis of the implications of recent financial crises affecting emerging economies in the 1990's points to the failure by private markets and other relevant institutions to meet the demand for cross-border and domestic short-term trade-finance in such periods, thereby affecting, in some countries and for certain periods, imports and exports to a point of stoppage. These experiences seem to suggest that there is scope for carefully targeted public intervention, as currently proposed by regional development banks and other actors, which have put in place ad-hoc schemes to maintain a minimum flow of trade finance during periods of scarcity, through systems of direct credit or credit guarantees. This paper explores the reasons behind the drying up of trade finance, both short and long-term, in particular as banks tend to concentrate on the more profitable and less risky segments of credit markets. It also describes ad-hoc schemes put in place by regional and multilateral institutions to keep minimal amounts of trade finance available at any time. It then goes on to examine a number of questions regarding the regulatory framework surrounding trade finance products, and looks at WTO rules in this regard. It also examines other areas where the WTO can play a role in facilitating and contributing to a global solution. In this context, a discussion of various proposals on the table is suggested.
Keywords: 330